Cost-effectiveness of antibiotic treatment of uncomplicated urinary tract infection in women: a comparison of four antibiotics. Issue 3 (2017) - Sadler, Susannah; Holmes, Michael; Ren, Shijie; Holden, Stephen; Jha, Swati; Thokala, Praveen
No abstract available